Climate catastrophe in Rio Grande do sul, Brazil: impact of strategic actions in response to flooding - Priscila Bárbara Zanini Rosa; Giovana Munhoz de Oliveira; Monique Pimentel; Melina Schuch; Jonas Wolf (BMC Research Notes)
Abstract Objective In May 2024, Rio Grande do Sul, Brazil, faced the greatest climate catastrophe in its history when a flood affected approximately 90% of the entire state territory. This study aimed to describe the strategic actions of volunteers gathered by a social institution linked to a private hospital in southern Brazil and their impacts on the affected community. Methods Descriptive study, based on the experience of the team at the Instituto Moinhos Social (IMS) - Hospital Moinhos de Vento (Rio Grande do Sul - Brazil), which brought together a group of volunteers to develop actions in response to the flood. Between 05/01/2024 and 07/31/2024, the IMS organized donations of basic items, health care, and monetary donations to recover goods for people affected by the flood. Results description The IMS had 583 volunteers working in the phase of receiving, organizing, and distributing donations and 208 health professionals for emergency care, mental health, and telemedicine. In total, approximately 317 thousand basic items were organized and distributed, which benefited almost 100 thousand people; 1044 people received health care; and 490 families received vouchers worth R$2,500 (US$455,66) for the recovery of material goods.